Classicism and Christianity in late antique Latin poetry - Hardie, Philip R. (Sather classical lectures, 2019)
Farewells and returns: Ausonius and Paulinus of Nola -- Virgilian plots -- Cosmos: classical and Christian universes -- Concord and discord; concordia discors -- Innovations of late antiquity: novelty and renouatio -- Paradox, mirabilia, miracles -- Allegory -- Mosaics and intertextuality.